A Multi-class Weight of Evidence Approach for Landslide Susceptibility Mapping Applied to an Area Along the EW Highway (Gerik–Jeli), Malaysia - Tareq Mezughi, Juhari Mat Akhir, Abdul Ghani Rafek, Ibrahim Abdu, . (2011)
The weights-of-evidence modelling (based on multi-class maps) was applied within a geographical information system (GIS) to prepare a landslide susceptibility map. The area selected is along the EW highway in Malaysia where frequent landslides occur. The spatial database for factors (evidences) that influence landslide occurrence were prepared from different sources including topographical maps, geological maps, satellite data, hydrological data, soil data and field data.